Kryzys gospodarczy 2007–2010 w debacie ekonomistów - Przesławska, Gabriela (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The purpose of the article is to characterise the chosen aspects of the economists’ debate over the current economic crisis concerning its core, the reasons of breakdown, evaluation of the applied remedies, and also the prospects of capitalism. The problem of “responsibility” of the economic science in the face of aforementioned issues and the new role of State in the modern economy is also considered. The topics enumerated above are considered in the context of the dispute between Keynesian and Neoclassical economists about the reasons of the present economic crisis and the validity of governments’ interventions to stabilize economies. Analysis of economists’ views concerning the core and origins of the recent economic and financial crisis and the purposefulness and effectiveness of the anti-crisis policy leads to conclusion, that the fundamental controversies between Keynesians and Neoclassical economists in the covered scope continue to exist. In the crisis diagnosis, Keynesians traditionally point out the market failures. On the contrary, Neoclassicists expose failures of the State
Keywords: Keynesian economists; neoclassical economists; economic crisis